Scene-selective coding by single neurons in the human parahippocampal cortex - Mormann, Florian; Kornblith, Simon; Cerf, Moran; Ison, Matias J.; Kraskov, Alexander; Tran, Michelle; Knieling, Simeon; Quian Quiroga, Rodrigo; Koch, Christof; Fried, Itzhak (National Academy of Sciences, 2017)
Imaging, electrophysiological, and lesion studies have shown a relationship between the parahippocampal cortex (PHC) and the processing of spatial scenes. Our present knowledge of PHC, however, is restricted to the macroscopic properties and dynamics of bulk tissue; the behavior and selectivity of single parahippocampal neurons remains largely unknown. In this study, we analyzed responses from 630 parahippocampal neurons in 24 neurosurgical patients during visual stimulus presentation. We found a spatially clustered subpopulation of scene-selective units with an associated event-related field potential. These units form a population code that is more distributed for scenes than for other stimulus categories, and less sparse than elsewhere in the medial temporal lobe. Our electrophysiological findings provide insight into how individual units give rise to the population response observed with functional imaging in the parahippocampal place area.